Pelatihan Pembuatan Suvenir dengan Teknik Sablon sebagai Produk Kreatif Kawasan Wisata Kota Tua Padang - Erniwati Erniwati; Zul Asri; Yelda Syafrina; Zulfa Saumia (RC-INSTITUT, 2020)
Padang Old Town area is one of the assets of cultural and historical tourism that must be developed. In the framework of developing the Old Town area along with the economic prospects, it is necessary to initiate a creative economic program that raises local values. For this reason, the campus community needs to take initiative and build synergies with the community in the Old Town area for the development of the creative economy. Through the partnership program that carries out screen printing training activities for souvenirs, it is hoped that products will emerge as new attractions for visitors to the Old Town area and entrepreneurs from the UNP students and the community will emerge.